Rooted in richness: unearthing the economic and ecological synergy of crop rotation - Cerveny, Jaroslav; Prochazka, Petr; Soukupova, Jana; Svoboda, Roman; Severova, Lucie; Smutka, Lubos; Cabelkova, Inna; Dvorak, Marek (Frontiers in Sustainable Food Systems, 2023)
Introduction This study deals with agricultural practices and their implications on soil health and crop yield using economic optimization. Specifically, the research focuses on the impact of different crops, such as canola, wheat, and meadow clover, on soil nitrogen levels and the subsequent effects on crop health. Methods A model of nitrogen flow is utilized while economic optimization is done using dynamic methods. Results The paper highlights the significance of the root system in crops like wheat and canola in determining the amount of organic residue left in the soil. Even though meadow clover stands out as a unique crop in the study, given its ability to fix atmospheric nitrogen without the need for fertilization given the economic variables, it is not selected in the mix. Discussion The findings of this research have implications for sustainable farming practices, emphasizing the balance between environmental protection and economic development. Our study shows in accordance with other studies that the use of canola leads to higher profits with consequent benefits for the next cereal crops.